Effectiveness of contralaterally controlled functional electrical stimulation vs. neuromuscular electrical stimulation for recovery of lower extremity function in patients with subacute stroke: A randomized controlled trial - Huang, Songhua; Zhang, Yuqian; Liu, Peile; Chen, Yinglun; Gao, Beiyao; Chen, Chan; Bai, Yulong (Frontiers in Neurology, 2022)
Objective This study aimed to compare the efficacy of contralaterally controlled functional electrical stimulation (CCFES) vs. neuromuscular electrical stimulation (NMES) for motor recovery of the lower extremity in patients with subacute stroke. Materials and methods Seventy patients within 6 months post-stroke were randomly assigned to the CCFES group (n = 35) and the NMES group (n = 35). Both groups underwent routine rehabilitation plus 20-min electrical stimulation (CCFES or NMES) on ankle dorsiflexion muscles per day, 5 days a week, for 3 weeks. Ankle AROM (dorsiflexion), Fugl-Meyer assessment-lower extremity (FMA-LE), Barthel Index (BI), Functional Ambulation Category scale (FAC), 10-meter walking test, and surface electromyography (sEMG) were assessed at the baseline and at the end of the intervention. Result Ten patients did not complete the study (five in CCFES and five in NMES), so only 60 patients were analyzed in the end. After the 3-week intervention, FMA-LE, BI, Ankle AROM (dorsiflexion), and FAC increased in both groups (p < 0.05). Patients in the CCFES group showed significantly greater improvements only in the measurement of Fugl-Meyer assessment-lower extremity compared with the NMES group after treatment (p < 0.05). The improvement in sEMG response of tibialis anterior by CCFES was greater than NMES (p < 0.05). Conclusion Contralateral controlled functional electrical stimulation can effectively improve the motor function of the lower limbs better than conventional neuromuscular electrical stimulation in subacute patients after stroke, but the effect on improving the ability to walk, such as walking speed, was not good. Clinical trial registration http://www.chictr.org.cn/, identifier: ChiCTR2100045423.